2007
DOI: 10.1021/ja073568h
|View full text |Cite
|
Sign up to set email alerts
|

Double−Step Gas Sorption of a Two−Dimensional Metal−Organic Framework

Abstract: The synthesis, structural changes, and nitrogen gas sorption isotherm of a porous metal−organic framework (PMOF) comprising stacked two-dimensional sheets are reported. This compound easily loses guest molecules and shrinks its interlayer distance. The guest-free species show a unique double-step sorption isotherm. Sorption and X-ray structural analyses have clarified that the first uptake is a micropore filling, while the second uptake originates from a clathrate formation. This explains the total sorption am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
140
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(148 citation statements)
references
References 14 publications
(14 reference statements)
7
140
0
Order By: Relevance
“…In contrast, the pressure at which we observe the step and hysteresis in the CO 2 isotherm is far below the saturation pressure (34.3 atm at 273 K), apparent in the high-pressure isotherms (see the Supporting Information). Similar behavior has been reported for the adsorption of nitrogen by a two-dimensional framework material [35] and by a three-dimensional pillared paddlewheel structure, but is otherwise unknown. [20,36] The N 2 and Ar isotherms of YO-MOF display a fairly unusual gated adsorption behavior (see Figure 4 and the Supporting Information).…”
Section: Resultssupporting
confidence: 74%
“…In contrast, the pressure at which we observe the step and hysteresis in the CO 2 isotherm is far below the saturation pressure (34.3 atm at 273 K), apparent in the high-pressure isotherms (see the Supporting Information). Similar behavior has been reported for the adsorption of nitrogen by a two-dimensional framework material [35] and by a three-dimensional pillared paddlewheel structure, but is otherwise unknown. [20,36] The N 2 and Ar isotherms of YO-MOF display a fairly unusual gated adsorption behavior (see Figure 4 and the Supporting Information).…”
Section: Resultssupporting
confidence: 74%
“…In fact, it was experimentally proven that this MOF showed high equilibrium and kinetic separation for CO 2 over CH 4 under realistic conditions, using a mixed gas at room temperature and in a humid environment (Figure 10b and c). The moderate heat of CO 2 adsorption (Q st = -18 to − 31 kJ mol − 1 ), which was experimentally determined, and the calculated interaction energy using a model structure (Figure 10d) 32 suggested that the fluorine atoms of the weakly coordinated PF 6 − anions contribute to the interaction sites with adsorbed CO 2 molecules. To elucidate the interactions between inorganic fluorinated monoanions and guest molecules in detail, it is important to determine the crystal structures with adsorbed guest molecules.…”
Section: Fluorine-functionalized Mofs/pcpsmentioning
confidence: 83%
“…31,53 After this finding, the derivatives [M(A) 2 (4,4′-bpy) 2 ] (M= Cu, A = CF 3 SO 3 ; M= Cu, A = PF 6 ; M = Co and A = CF 3 SO 3 ) were separately reported. [32][33][34] These MOFs formed similar two-dimensional square-grid frameworks with weakly coordinated CF 3 SO 3 − and PF 6 − (Cu), and coordinated CF 3 SO 3 − (Co) monoanions but showed different sorption behaviors from the parent ELM-11; there were two sorption events: the first uptake was a micropore filling and the second uptake was caused by a gate-sorption process with an expansion of the interlayer distance and sliding between the layers. Using these anions, it is also possible to fabricate one-dimensional flexible MOFs exhibiting gate sorption.…”
Section: Fluorine-functionalized Mofs/pcpsmentioning
confidence: 99%
“…Many flexible MOFs exhibit an interesting gate-opening phenomenon where the framework structures suddenly changes from a relatively closed structure to an open one and due to guest-induced framework transition [44,[58][59][60][61]. Kitagawa Inspection of Fig.…”
Section: Absence Of Gate-opening Phenomenon?mentioning
confidence: 99%